Pengetahuan dan Sikap Pasangan Usia Subur Tentang Infertilitas di Praktek Dokter Ihsan Suheimi, SpOG Pekanbaru Tahun 2018 - Mona Dewi Utari (STIKes Al-Insyirah Pekanbaru, 2019)
According to the Word Health Organization (WHO) it is estimated that (8-10%) couples in the world have a history of difficult to obtain children. Infertility rates in Indonesia range (12-15%). The number of infertility couples in Indonesia can be calculated from the number of women who have ever married and do not have children who are still alive. This study was conducted with the aim to determine the description of Knowledge and Attitudes of Fertile Couples About Infertility in Doctor Practices Ihsan Suheimi, Pekanbaru SpOG in 2018. Infertility is a condition that shows no conception within one year after sexual intercourse without contraceptive protection. The research design was descriptive research, using accidental sampling techniques, from June to December 2018 as many as 60 couples of childbearing age. Data in this study were obtained from primary data obtained from questionnaires that were distributed directly to respondents. From the research it was found that out of 60 respondents of EFA the majority of knowledgeable husbands were less than 44 respondents (72.1%), while less knowledgeable wives were 37 respondents (61.6%), and all PUS have a positive attitude about infertility, each of which is 60 respondents (100%). And it is hoped that couples of childbearing age can increase their knowledge from various sources and to health workers to more often disseminate information about infertility